From Climate Change to Corona: The Shift in Focus of Media Coverage During the First Wave of the Corona Pandemic in Germany - Krug, Maximilian; Kuhn, Paula; Lauschner, Leonie; Mercsak, Aylin; Schulte-Zweckel, Nora (Momentum Quarterly, 2021)
The Covid-19 pandemic has a significant impact on society as a global crisis. We question whether the media covers Covid-19 in a similar or even higher frequency than the longstanding climate crisis. In terms of framing, this paper examines how Corona and climate change displace each other during the first wave of the Corona pandemic in Germany. The study focuses on cross-media and media-specific framing processes and derives policy implications from the findings. Data basis is 15,038 articles of daily newspapers and news service posts on social media. The evaluation of our data demonstrates that the media coverage of Covid-19 has quantitatively and qualitatively driven out the topic of environment during the first wave in Germany. Thematic displacement harbors the danger of one-sided reporting and is discussed in concerning their socio-political implications.
Keywords: corona; covid-19; climate crisis; media frames; agenda setting; content analysis